IMPLEMENTASI MODEL PROJECT-BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS, KREATIF, DAN KOLABORATIF SISWA DALAM MENYELESAIKAN MASALAH NYATA - Yeyen Herlina (JOURNAL OF COMMUNITY DEDICATION, 2025)
This study aims to analyse the implementation of the Project-Based Learning (PjBL) model in improving students' critical, creative, and collaborative thinking skills in solving real-world problems. The method used is a literature review by collecting and analysing various relevant literature sources. The results of the study indicate that PjBL is effective in encouraging students to think analytically, develop innovative ideas, and work together in teams through direct experience in working on real projects. The role of teachers as facilitators is very important in directing the learning process so that the objectives of developing thinking and collaboration skills are achieved properly. Thus, PjBL contributes significantly to shaping essential 21st-century skills for students' readiness to face real-world challenges.